Dinuclear ruthenium sawhorse-type complexes containing carboxylato bridges and ferrocenyl substituents: Synthesis and electrochemistry - Auzias, Mathieu; Süss-Fink, Georg; Štěpnička, Petr; Ludvík, Jiří (My University, 2007)
The ferrocenyl-containing diruthenium complexes [Ru2(CO)4(μ2-η2-OOCFc)2L2] (Fc = ferrocenyl, fc = ferrocen-1,1′-diyl; 1: L = NC5H4–COOC6H4–OC10H21, 2: L = NC5H4–COOC6H4–OC16H33, 3: L = NC5H4–OOC–fc–C12H25) and [Ru2(CO)4(μ2-η2-OOC6H5)2(NC5H4–OOC–fc–C12H25)2] (4) have been synthesized from Ru3(CO)12, ferrocene carboxylic or benzoic acid and the corresponding pyridine derivative. The synthesis of the new pyridine derivative NC5H4–OOC–fc–C12H25 used for the preparation of 3 and 4 is also reported. Complexes 1–4 posses a so-called sawhorse structure consisting of the Ru2(CO)4 backbone and two bridging carboxylato ligands, while the coordination sphere around the ruthenium atoms is completed by the pyridine-derived ligands bonded in the axial positions. The electrochemical behavior of 1–4 and their known analogues [Ru2(CO)4(μ2-η2-OOCFc)2L2] (5: L = NC5H5, 6: L = P(C6H5)3, 7: L = NC5H4–OOCFc) has been studied by voltammetry on rotating disc electrode and by cyclic voltammetry.
Keywords: carboxylato bridges; dinuclear complexes; ruthenium; ferrocene; electrochemistry